Musik Langgam Jawa untuk Menurunkan Kecemasan pada Pasien Pre Operasi - Aries Triatna; Adi Sucipto; Cristin Wiyani (Politeknik Kesehatan Tanjung Karang, 2018)
The most common response by preoperative patients is anxiety. The results of research on the incidence of anxiety in preoperative patients in RS PKU Yogyakarta mentioned that 60% of patients experience anxiety from mild to severe level (Wuryani, 2015). There are several ways to reduce anxiety, one of them is by giving music therapy. Based on the result of interviews with five patients who were going to have an operation, the patients expressed that they were anxious because they were afraid of the operation and that was worried if the operation may fail. To determine whether three is an influence of listening to “Langgam Jawa” music genre on the level of anxiety of preoperative patients at “Kasuari” room of RSPAU, dr. S. Hardjolikito. This is a quasi-experiment research which used a pre-test and post-test non-equivalent control group design. There were 30 respondents involved as samples. The samples were selected using a systematic random sampling technique. The instrument used in this research waZung’s self-rating anxiety scale (SAS). The statistical test used a Wilcoxon signed rank test with an error level of 0.05. In the control group, which was not given “langgam jawa” music, during pre-test most patients experienced medium level anxiety (26,7%), during post-test most patients experienced medium level anxiety (60%); in the intervention group, before “langgam jawa” music treatment was given, most patients experienced medium level of anxiety (26,7%), after the music treatment was given, most patients experienced a medium level of anxiety (56,7%). Based on the research result, there is a significant influence from “langgam jawa: music therapy with a p-value=0.007. There is an influence of listening to “langgam jawa” music genre on the level of anxiety of preoperative patients at “Kasuari” Ward, dr. S. Hardjolikito Hospital.